Share the dream : a song for the XVIth Commonwealth Games - Tan, Boon; Khaw, Freddie; Broadway Entertainment (Malaysia).; BMG Music (Kuala Lumpur : Broadway Entertainment (M), 1998)
Contains three tracks dedicated to the 16th Commonwealth Games.
CD 1 : Share The Dream (Full Mix) -- Share The Dream (Orchestral Mix) -- Share The Dream (Minus One Mix).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Music festivals